A DFT study of proton transfers for the reaction of phenol and hydroxyl radical leading to dihydroxybenzene and H2O in the water cluster. Issue 6 (9th October 2017) - Yamabe, Shinichi; Yamazaki, Shoko
Abstract: Reactions of phenol and hydroxyl radical were studied under the aqueous environment to investigate the antioxidant characters of phenolic compounds. M06‐2X/6‐311 + G(d, p) calculations were carried out, where proton transfers via water molecules were examined carefully. Stepwise paths from phenol + OH + (H2 O) n ( n = 3, 7, and 12) to the phenoxyl radical (PhO ) via dihydroxycyclohexadienyl radicals ( ipso, ortho, meta, and para OH‐adducts) were obtained. In those paths, the water dimer was computed to participate in the bond interchange along hydrogen bonds. The concerted path corresponding to the hydrogen atom transfer (HAT, apparently PhOH + OH → PhO + H2 O) was found. In the path, the hydroxyl radical located on the ipso carbon undergoes the charge transfer to prompt the proton (not hydrogen) transfer. While the present new mechanism is similar to the sequential proton loss electron transfer (SPLET) one, the former is of the concerted character. Tautomerization reactions of ortho or para (OH)C6 H5 =O + (H2 O) n → C6 H4 (OH)2 (H2 O) n were traced with n = 2, 3, 4, and 14. The n = 3 (and n = 14) model of ortho and para was calculated to be most likely by the strain‐less hydrogen‐bond circuit. Abstract : First‐principles calculations provide valuable insight into the mechanism of the reactions between phenol and hydroxyl radical. Under aqueous environment, reaction modeling reveals the antioxidant characters of phenolic compounds. Transition states involving proton transfers for elementary processes were determined for this class of reactions by density functional theory calculations.